Harnessing Metal Homeostasis Offers Novel and Promising Targets Against Candida albicans - Hameed, Saif; Hans, Sandeep; Singh, Shweta; Fatima, Zeeshan (Current Drug Discovery Technologies, 2020)
Fungal infections, particularly of Candida species, which are the commensal organisms of human, are one of the major debilitating diseases in immunocompromised patients. The limited number of antifungal drugs available to treat Candida infections, with the concomitant increasing incidence of multidrug-resistant (MDR) strains, further worsens the therapeutic options. Thus, there is an urgent need for the better understanding of MDR mechanisms, and their reversal, by employing new strategies to increase the efficacy and safety profiles of currently used therapies against the most prevalent human fungal pathogen, Candida albicans. Micronutrient availability during C. albicans infection is regarded as a critical factor that influences the progression and magnitude of the disease. Intracellular pathogens colonize a variety of anatomical locations that are likely to be scarce in micronutrients, as a defense strategy adopted by the host, known as nutritional immunity. Indispensable critical micronutrients are required both by the host and by C. albicans, especially as a cofactor in important metabolic functions. Since these micronutrients are not freely available, C. albicans need to exploit host reservoirs to adapt within the host for survival. The ability of pathogenic organisms, including C. albicans, to sense and adapt to limited micronutrients in the hostile environment is essential for survival and confers the basis of its success as a pathogen. This review describes that micronutrients availability to C. albicans is a key attribute that may be exploited when one considers designing strategies aimed at disrupting MDR in this pathogenic fungi. Here, we discuss recent advances that have been made in our understanding of fungal micronutrient acquisition and explore the probable pathways that may be utilized as targets.
Keywords: magnesium and manganese.MDR